2018
DOI: 10.1093/jee/toy205
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization Increases the Nutritional Quality of Aphis gossypii (Hemiptera: Aphididae) as Prey for Hippodamia variegata (Coleoptera: Coccinellidae) and Alters Predator Foraging Behavior

Abstract: Nitrogen (N) fertilization is a common agricultural practice, which, by increasing the quality of plants, also enhances their nutritional suitability for insect herbivores, creating the possibility of a cascade of N across trophic levels, from plant to herbivore to predator. We manipulated the quality of cucumber plants by fertilizing them with three different N rates (110, 160, and 210 ppm), which represented low, medium, and high N levels, respectively. Colonies of Aphis gossypii Glover (Hemiptera: Aphididae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
0
4
0
4
Order By: Relevance
“…Similar to our study, Alizade et al (2016) showed enhanced life history performance and population growth of T. urticae on N-fertilized strawberry plants. Increasing N content of the host plant tissue via chemical N fertilization improved the availability of dietary proteins, which typically benefits herbivores such as two-spotted spider mites ( Alizade et al, 2016 ; Hosseini et al, 2018 ). Beneficial soil bacteria commonly also improve plant nutrition via increasing the uptake and concentration of a variety of nutrients, including nitrogen, and might also enhance the production of phytohormones that promote growth indicators like the rate of photosynthesis activity ( Zhang et al, 2008 ; Pineda et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Alizade et al (2016) showed enhanced life history performance and population growth of T. urticae on N-fertilized strawberry plants. Increasing N content of the host plant tissue via chemical N fertilization improved the availability of dietary proteins, which typically benefits herbivores such as two-spotted spider mites ( Alizade et al, 2016 ; Hosseini et al, 2018 ). Beneficial soil bacteria commonly also improve plant nutrition via increasing the uptake and concentration of a variety of nutrients, including nitrogen, and might also enhance the production of phytohormones that promote growth indicators like the rate of photosynthesis activity ( Zhang et al, 2008 ; Pineda et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…De beschikbaarheid van stikstof in de vorm van vrije aminozuren wordt beïnvloed door het stikstofgehalte dat aan planten wordt geleverd. Lagere stikstofgehalten resulteren in het algemeen in een lagere reproductiesnelheid van bladluizen (Harrewijn 1983, Petitt et al 1994, Hosseini et al 2018.…”
Section: Plantenvoedingunclassified
“…Plantenvoeding in het algemeen heeft grote invloed op de kwaliteit en voedingswaarde van herbivoren voor natuurlijke vijanden en kan dus indirect grote effecten op biologische bestrijding hebben (Fagan et al 2002, Chen et al 2010. Bladluizen van planten met weinig voeding zijn kleiner en minder voedzaam voor predatoren dan die van met stikstof bemeste planten (Couture et al 2010, Hosseini et al 2018. Dit geeft aan dat een lager stikstofgehalte niet alleen de bladluisdichtheid kan verminderen, maar ook de bladluisconsumptie door predatoren kan verhogen, wat dus gunstig is voor de biologische bestrijding van bladluis.…”
Section: Plantenvoedingunclassified
“…Hiervan ging bijna de helft van de studies over de effecten van bemesting op sluipwespen Krauss et al 2007;Sarfraz et al 2009;Staley et al 2011;Pope et al 2012;Aqueel et al 2015;Chesnais et al 2016;Mace et al 2016;Dong et al 2018;Pekas et al 2020;Liu et al 2017;de Oliveira et al 2020), waren er 4 studies over de effecten van bemesting op miride roofwantsen (Han et al 2015a;Han et al 2015b. ;Liman et al 2017;Zhu et al 2020), 2 studies over de effecten van bemesting op Orius roofwantsen (Hosseini et al 2010;Groenteman et al 2016;), twee studies over de effecten van bemesting op lieveheersbeestjes (Couture et al 2010;Hosseini et al 2018), en 3 studies over de effecten van bemesting op het gedrag van en/of de plaagbestrijding door roofmijten (Chow et al 2009;Chow et al 2012;Islam et al 2021). Verreweg de meeste studies die hebben gekeken naar natuurlijke vijanden gingen over de effecten van stikstof bemesting (15 studies).…”
Section: Effecten Van Silicium (Si) Op Plaagorganismenunclassified